Social Network Site (SNS) appropriation process in family perspective based on family types - Mahmud, Y. (Asian Research Publishing Network, 2016)
Many previous researchers have highlighted the positive and negative impacts of SNS usage in family environment such as improving family communications and bonding or worsen the family relationships. These impacts would varies depending on the family relationships. However, studies on SNS adoption, adaptation and use according to different types of family relationships have received little research attention. Eleven actual case studies which involved 31 respondents were selected. The data collection were conducted through interviews, observations and content analysis to achieve the main research objectives of why and how do family members adopt, adapt and use SNS according to different types of family groups. Results from the data collection were used in the development of Family Appropriation Process of Social Network Site (FAPSNS) framework which also facilitated in the understanding of SNS appropriation process criteria in family, individual, technical and extra-familial perspectives. The current level of SNS appropriation according to family groups namely Modern, Chummy and Mixed families are also identified. However, this paper is focusing on the SNS appropriation process in family perspective only. The results highlighted that Modern family has successfully appropriated Facebook at Level 3 of family perspectives. Whereas, Chummy and Mixed families have disappropriated Facebook at Level 2 in family perspective.